Decoupled phase transitions and grain-boundary melting in supported phospholipid bilayers - Keller, Danielle; Larsen, Niels B; Møller, Ian M; Mouritsen, Ole G (Physical review letters, 2005)
Two separate liquid-solid phase transitions are detected in the two monolayers of a mica-supported phospholipid bilayer by atomic force microscopy. The phase transitions of the two monolayers are decoupled by the stronger interaction between the lipid headgroups of the proximal monolayer and the mica support. The transition temperature of the proximal monolayer is increased and this transition occurs over a narrower temperature range. Both transitions occur via grain-boundary melting and the variation of the width of the interfacial zone with temperature is consistent with mean-field theory.